Vietnam Food Safety Risks Management : Challenges and Opportunities - World Bank (World Bank, Hanoi, 2017)
In Vietnam, food safety is of great and increasing importance to consumers and policymakers alike. The Government of Vietnam requested the World Bank and other development partners for assistance in assessing food safety risks an din providing policy recommendations on how to improve food safety risk management. To this end, a series of activities, including a literature review, field visits, round-table discussions and interviews with experts and consultations were held between January and July 2016. While food safety was broadly addressed, the emphasis of this review was on domestic urban markets with a special focus on pork and leafy vegetable value chains supplying Ha Noi and H Chi Minh City. This report presents the key findings to help identify priorities and practical solutions to address foo safety.